2020
DOI: 10.5114/bta.2020.94774
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound conditioning of Streptococcus thermophilus CNRZ 447: growth, biofilm formation, exopolysaccharide production, and cell membrane permeability

Abstract: Sonication is one of the new and innovative approaches that is being increasingly used in food industry to control fermentation processes and to eradicate spoiling. Recently, this approach has seen new industrial applications such as enhancing microbial productivity. The present study aimed to assess the effects of ultrasound conditioning on the metabolism and extracellular matrix production of Streptococcus thermophilus. Bacterial suspensions were treated in ultrasonic bath (35 kHz, 240/60 W peak/nominal powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The production of EPS by L. bulgaricus strains has been reported previously [46] . For instance, Khadem, Tirtouil, Drabo and Boubakeur [47] also showed that S. thermophilus strain had important potential to produce EPS. They reported that using ultrasound for a certain period of time could increase the production of EPS by this strain.…”
Section: Resultsmentioning
confidence: 99%
“…The production of EPS by L. bulgaricus strains has been reported previously [46] . For instance, Khadem, Tirtouil, Drabo and Boubakeur [47] also showed that S. thermophilus strain had important potential to produce EPS. They reported that using ultrasound for a certain period of time could increase the production of EPS by this strain.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the positive effect on biofilm stability, mainly found on L. plantarum DSM 1055, could also involve other phenomena, like the increased nutrients transport to deeper layers of the biofilm ( Peterson and Pitt, 2000 ; Erriu et al, 2014 ), as well as by a probable effect on membrane permeability, and exopolysaccharide production ( Khadem et al, 2020 ). In fact, it is reliable to assume that a good diffusion of nutrients across biofilm could delay cell aging, and consequently their detachment from the adhesion surface.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial cells were collected, washed twice in saline, and resuspended in 1 M NaCl solution. Then, surface substances, including CPSs and SPs, were stripped with ultrasonic treatment [ 21 ]. By adjusting the operating frequencies and times, the most appropriate conditions were determined in which the bacteria could survive well, and their surface substance would be stripped completely.…”
Section: Methodsmentioning
confidence: 99%